Genetic Engineering of Lactococcus lactis Co-producing Antigen and the Mucosal Adjuvant 3′ 5′- cyclic di Adenosine Monophosphate (c-di-AMP) as a Design Strategy to Develop a Mucosal Vaccine Prototype - Quintana, Ingrid; Espariz, Martín; Villar, Silvina R.; González, Florencia B.; Pacini, Maria F.; Cabrera, Gabriel; Bontempi, Iván; Prochetto, Estefanía; Stülke, Jörg; Perez, Ana R.; Marcipar, Iván; Blancato, Victor; et al. (Frontiers in Microbiology, 2018)
Lactococcus lactis is a promising candidate for the development of mucosal vaccines. More than 20 years of experimental research supports this immunization approach. In addition, 3´ 5´- cyclic di-adenosine monophosphate (c-di-AMP) is a bacterial second messenger that plays a key role in the regulation of diverse physiological functions (potassium and cellular wall homeostasis, among others). Moreover, recent studies showed that c-di-AMP has a strong mucosal adjuvant activity that promotes both humoral and cellular immune responses. In this study, we report the development of a novel mucosal vaccine prototype based on a genetically engineered L. lactis strain. First, we demonstrate that homologous expression of cdaA gene in L. lactis is able to increase c-di-AMP levels. Thus, we hypothesized that in vivo synthesis of the adjuvant can be combined with production of an antigen of interest in a separate form or jointly in the one same strain. Therefore, a specifically designed fragment of the trans-sialidase (TScf) enzyme from the Trypanosoma cruzi parasite, the etiological agent of Chagas disease, was selected to evaluate as proof of concept the immune response triggered by our vaccine prototypes. Consequently, we found that oral administration of a L. lactis strain expressing antigenic TScf combined with another L. lactis strain producing the adjuvant c-di-AMP could elicit a TS-specific immune response. Also, an additional L. lactis strain containing a single plasmid with both cdaA and tscf genes under the Pcit and Pnis promoters respectively, was also able to elicit a specific immune response. Thus, the current report is the first one to describe an engineered L. lactis strain that simultaneously synthesizes the adjuvant c-di-AMP as well as a heterologous antigen in order to develop a simple and economical system for the formulation of vaccine prototypes using a food grade lactic acid bacterium.